2014
DOI: 10.1097/gco.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro maturation of germinal vesicle and metaphase I eggs prior to cryopreservation optimizes reproductive potential in patients undergoing fertility preservation

Abstract: Conservation of retrieved immature oocytes after vaginal oocyte retrieval has become a major concern for patients, as they strive to maximize the reproductive viability of all oocytes obtained during treatment. Oocyte cryopreservation is important for patients at risk of ovarian cancer, elective fertility preservation and potentially for ovum donation. The superior maturation rate of germinal vesicle and metaphase I oocytes in the fresh IVM vs. postthaw groups provides strong impetus to mature oocytes to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Although nowadays comparable high survival rates (80-85%) have been reported for oocytes vitrified prior to or post-IVM [43,44], differences found in terms of cellular alterations and clinical outcomes claim for an impairment in the ability of human IVM oocytes to mature, fertilize, and cleave, that seems to be dependent on the stage in which vitrification occurs.…”
Section: Oocyte In Vitro Maturation Prior To and Post-vitrificationmentioning
confidence: 85%
See 1 more Smart Citation
“…Although nowadays comparable high survival rates (80-85%) have been reported for oocytes vitrified prior to or post-IVM [43,44], differences found in terms of cellular alterations and clinical outcomes claim for an impairment in the ability of human IVM oocytes to mature, fertilize, and cleave, that seems to be dependent on the stage in which vitrification occurs.…”
Section: Oocyte In Vitro Maturation Prior To and Post-vitrificationmentioning
confidence: 85%
“…However, even if oocyte morphology and zona pellucida birefringence were not altered [51,52], the maturation potential was reduced by Cryotop vitrification of human immature GV-stage oocytes, as seen by reduced maturation rate and oocyte viability respect to the fresh counterpart [36,53]. Superior maturation rates of GV and MI oocytes vitrified post-IVM (≈ 64%), have been demonstrated in terms of mitochondria, chromatin, and spindle formation, respect to those vitrified prior to IVM (≈ 33%) [44]. Moreover, no detrimental effects were seen on the meiotic spindle configuration between oocytes matured in vitro and those vitrified after IVM [32].…”
Section: Oocyte In Vitro Maturation Prior To and Post-vitrificationmentioning
confidence: 99%
“…The maturation rate following thawing and IVM after vitrification at the GV stage is 50.8%, significantly lower than the rate of 70.4% for the IVM of fresh material . Several reports have yielded consistent results; therefore, it is common to cryopreserve matured oocytes when using the vitrification method.…”
Section: Cryopreservation Of Oocytes For Fertility Preservationmentioning
confidence: 97%
“…A number of groups have reported effects of cryopreservation of GV stage oocytes. The effects of slow freezing are controversial: two studies showed that slow freezing at GV stage had better outcome than at post-IVM MII stage [ 16 , 17 ], while several other studies reported low maturation rates when slow freezing at the GV stage was performed [ 18 , 19 , 33 ]. Vitrification at GV stage was reported to negatively affect maturation rates [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%